Prenatal Alcohol Consumption Between Conception and Recognition of Pregnancy. (24th January 2017) - McCormack, Clare; Hutchinson, Delyse; Burns, Lucy; Wilson, Judy; Elliott, Elizabeth; Allsop, Steve; Najman, Jake; Jacobs, Sue; Rossen, Larissa; Olsson, Craig; Mattick, Richard
Abstract : Background: Current estimates of the rates of alcohol‐exposed pregnancies may underestimate prenatal alcohol exposure if alcohol consumption in early trimester 1, prior to awareness of pregnancy, is not considered. Extant literature describes predictors of alcohol consumption during pregnancy; however, alcohol consumption prior to awareness of pregnancy is a distinct behavior from consumption after becoming aware of pregnancy and thus may be associated with different predictors. The purpose of this study was therefore to examine prevalence and predictors of alcohol consumption by women prior to awareness of their pregnancy, and trajectories of change to alcohol use following pregnancy recognition. Methods: Pregnant women ( n = 1, 403) were prospectively recruited from general antenatal clinics of 4 public hospitals in Australian metropolitan areas between 2008 and 2013. Women completed detailed interviews about alcohol use before and after recognition of pregnancy. Results: Most women ( n = 850, 60.6%) drank alcohol between conception and pregnancy recognition. Binge and heavy drinking were more prevalent than low‐level drinking. The proportion of women who drank alcohol reduced to 18.3% ( n = 257) after recognition of pregnancy. Of women who drank alcohol, 70.5% ceased drinking, 18.3% reduced consumption, and 11.1% made no reduction following awareness of pregnancy. Socioeconomic status (SES) was the strongest predictor of alcohol use, with drinkers more likely to be of high rather than low SES compared with abstainers (OR = 3.30, p < 0.001). Factors associated with different trajectories (either cessation, reduction, or continuation of drinking) included level of alcohol use prior to pregnancy recognition, age, pregnancy planning, and illicit substance use. Conclusions: In this sample of relatively high SES women, most women ceased or reduced drinking once aware of their pregnancy. However, the rate of alcohol‐exposed pregnancies was higher than previous estimates when the period prior to pregnancy recognition was taken into account. Abstract : The early stages of pregnancy, between conception and pregnancy recognition, appear at highest risk of alcohol exposure. Data from 1403 women recruited from antenatal clinics showed alcohol use was common, exceeding previous estimates, when this period prior to pregnancy recognition was considered. However, most women ceased or reduced drinking once becoming aware of pregnancy. Women who drank were more socioeconomically advantaged than those who did not. Further research involving underrepresented low SES, rural, and indigenous populations would be informative.